Increased problematic smartphone use among children with attention-deficit/hyperactivity disorder in the community: The utility of Chinese version of Smartphone Addiction Proneness Scale - Huang, Yu-Chieh; Hu, Sz-Chi; Shyu, Li-Yu; Yeh, Chin-Bin (Journal of the Chinese Medical Association, 2020)
Problematic smartphone use is more prevalent in children than before. This study aimed to evaluate the reliability and validity of the Chinese version of the Smartphone Addiction Proneness Scale (SAPS). We recruited 319 students aged 9 to 12 years including 70 attention-deficit/hyperactivity disorder subjects at a university hospital and 249 controls from elementary school. Finally, 164 males and 138 females were collected for data analysis with mean age of 10.99 ± 0.88 years. Item analysis, exploratory factor analysis, internal consistency test, and t test were performed to verify the reliability and validity of the SAPS-Chinese version. Correlations were examined for relation between the score in the SAPS-Chinese version and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition diagnostic criteria. Factor analysis showed two factors: problematic use-associated behaviors and impaired daily functions. Item analysis for every item in the SAPS-Chinese version showed significant differences in t values (p < 0.001) and high correlation in all items (r = 0.37-0.79). The Kaiser-Meyer-Olkin (KMO) was equal to 0.94 and Bartlett's test of Sphericity was significant (p < 0.001). Cronbach's α for the SAPS-Chinese version was 0.93. It revealed high reliability and validity. The SAPS-Chinese version is reliable, valid, and suitable for clinical and research uses with satisfactory properties. Applying the modified SAPS-Chinese version offers early detection of problematic smartphone use.